Ultrafast Spectral Tuning of a Fiber Laser for Time-Encoded Multiplex Coherent Raman Scattering Microscopy - Gottschall, Thomas; Meyer-Zedler, Tobias; Eibl, Matthias; Pfeiffer, Tom; Hakert, Hubertus; Schmitt, Michael; Huber, Robert; Tünnermann, Andreas; Limpert, Jens; Popp, Jürgen (Journal of Physical Chemistry B, 2023)
Coherent Raman scattering microscopy utilizing bioorthogonal tagging approaches like isotope or alkyne labeling allows for a targeted monitoring of spatial distribution and dynamics of small molecules of interest in cells, tissues, and other complex biological matrices. To fully exploit this approach in terms of real-time monitoring of several Raman tags, e.g., to study drug uptake dynamics, extremely fast tunable lasers are needed. Here, we present a laser concept without moving parts and fully electronically controlled for the quasi-simultaneous acquisition of coherent anti-Stokes Raman scattering images at multiple Raman resonances. The laser concept is based on the combination of a low noise and spectrally narrow Fourier domain mode-locked laser seeding a compact four wave mixing-based high-power fiber-based optical parametric amplifier.
CRIS-Team Scopus Importer:2023-04-20